Global action for sustainable rangelands and pastoralism to achieve Land Degradation Neutrality (LDN): Working paper - Louhaichi, Mounir; Masumbuko, Bora; Herrera, Pedro; Niamir-Fuller, Maryam; Liniger, Hanspeter; Mekdaschi-Studer, Rima; Badripour, Hossein; Bendandi, Barbara Bendandi; Cesaro, Jean-daniel; Chavez, Eric; Harari, Nicole; Getahun, Tezera; et al. (International Year of Rangelands and Pastoralists, 2024)
This is a working paper on a science-to-policy review, with recommendations for the UNCCD Conference of the Parties, prepared by the IYRP Rangelands & Land Degradation Neutrality Working Group.